12 American detective stories - Hoch, Edward D. (Oxford University Press, 1997)
Murder, kidnapping, and theft are the principal crimes committed in these twelve American detective stories. The victim may be an innocent baby or a double-crossing mobster, the setting a department store or death cell at the state prison. However, the detectives intellectual and intuitive powers must be unfailing, whether the important clue is a single bullet or a tiny splinter of wood.